Penerapan Metode Pembelajaran Make A Match Untuk Meningkatkan Motivasi Dan Hasil Belajar IPS Pada Siswa Madrasah Tsanawiyah Miftahul Falah Jakarta - Kartika Mariskhana (Cakrawala - Jurnal Humaniora, 2020)
This study aims to 1) increase social studies motivation and learning outcomes through the application of cooperative learning methods make a match in class VII students of Madrasah Tsanawiyah Miftahul Falah Jakarta 2019/2020 Academic Year. 2) improve the learning outcomes of social studies through the application of cooperative learning methods make a match to students of class VII Madrasah Tsanawiyah Miftahul Falah Jakarta 2019/2020 Academic Year. This research is a class action research. This research was conducted at the Madrasah Tsanawiyah Miftahul Falah Jakarta in 2019/2020 Academic Year. The subjects in this study were class VII students, amounting to 34 students. Data collection techniques in this study used a questionnaire, observation and tests. Data analysis techniques using quantitative and qualitative descriptive with percentages. The results showed that 1) The use of cooperative learning make a match learning method can increase students' learning motivation especially in Class VII Madrasah Tsanawiyah Miftahul Falah students in Jakarta, as evidenced in pre-cycle students who have learning motivation with a good minimum category reaching 38.24% increased in the first cycle 61.76% and in the second cycle 82.35%. 2) The use of cooperative learning methods make a match can improve student learning outcomes, especially in students of Class VII Madrasah Tsanawiyah Miftahul Falah Jakarta, this can be seen in completeness of student learning, in pre-cycle students who achieve KKM scores of 12 students (35.29% ), increased in the first cycle to 17 students (50%) and in the second cycle increased to 29 students (85.29%). Keywords: make a match method, motivation, learning outcomes.